Study of phenolphthalein received in bribe trap cases by various analytical techniques - ASTHA PANDEY; VISHALA PITHAVA (International Journal of Pharma and Bio Sciences, 2018)
Bribery is defined as the offering, giving, receiving or soliciting of any precious item for unauthorized work. To deal with these types of crime, many of law enforcement agencies usually arrange the trap in which they used certain chemicals which help to trap the person while taking the money. There are innumerable bribe trap cases which are received in the Forensic Science Laboratories. Present article is based on the qualitative analysis of phenolphthalein powder used in bribe trap cases. In the present study analytical methods like TLC (Thin Layer Chromatography), UV-VIS spectroscopy, FTIR (Fourier Transform Infrared spectroscopy), HPLC (High Performance Liquid Chromatography) were explored. From this study, it can be concluded that all the analytical methods are best suited for the analysis of phenolphthalein. For HPLC, Acetonitrile: Distilled Water with few drops of 0.1M acetic acid (100:900) was used in isocratic mode and retention time was obtained at 2.63. Thus, the above solvent system developed for HPLC was a modified new method which could be used for the detection of phenolphthalein. Further detailed studies are required to be explored in the area of phenolphthalein detection.